Which technology to select for primary focal treatment of prostate cancer?: European Section of Urotechnology (ESUT) position statement - Ganzer, Roman; Teber, Dogu (Prostate cancer and prostatic diseases, 2018)
With growing interest in focal therapy (FT) of prostate cancer (PCa) there is an increasing armamentarium of treatment modalities including high-intensity focused ultrasound (HIFU), cryotherapy, focal laser ablation (FLA), irreversible electroporation (IRE), vascular targeted photodynamic therapy (VTP), focal brachytherapy (FBT) and stereotactic ablative radiotherapy (SABR). Currently there are no clear recommendations as to which of these technologies are appropriate for individual patient characteristics. Our intention was to review the literature for special aspects of the different technologies that might be of advantage depending on individual patient and tumour characteristics. The current literature on FT was screened for the following factors: morbidity, repeatability, tumour risk category, tumour location, tumour size and prostate volume and anatomical issues. The ESUT expert panel arrived at consensus regarding a position statement on a structured pathway for available FT technologies based on a combination of the literature and expert opinion. Side effects were low across different studies and FT modalities with urinary continence rates of 90-100% and erectile dysfunction between 5 and 52%. Short to medium cancer control based on post-treatment biopsies were variable between ablative modalities. Expert consensus suggested that posterior lesions are better amenable to FT using HIFU. Cryotherapy provides best possible outcomes for anterior tumours. Apical lesions, when treated with FBT, may yield the least urethral morbidity. Further prospective trials are required to assess medium to long term disease control of different ablative modalities for FT. Amongst different available FT modalities our ESUT expert consensus suggests that some may be better for diffe`rent tumour locations. Tumour risk, tumour size, tumour location, and prostate volume are all important factors to consider and might aid in designing future FT trials.